2019
DOI: 10.1002/suco.201900024
|View full text |Cite
|
Sign up to set email alerts
|

Energy dissipation and self‐centering capacities of posttensioning precast segmental ultra‐high performance concrete bridge columns

Abstract: The research aims to better balance energy dissipation (ED) and self-centering capacities of posttensioning (PT) precast segmental ultra-high performance concrete bridge columns by adjusting common design parameters. A numerical model is established based on the equivalent plastic hinge model and validated by the cyclic loading test. The validated model is used to conduct a parametric study to investigate the effects of seven common design parameters on ED and self-centering capacities. The results show the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…(3) Estimating the equivalent viscous damping of the structural system:After installing the viscoelastic damper, the damper further provides additional damping to the structure. e nonlinear hysteretic damping of self-centring structures can be calculated by the hysteretic loop curve obtained from the nonlinear analysis of the structure [16] and the calculation method for the additional damping from viscoelastic dampers based on the method derived in the previous section. (4) Determining the effective viscous damping: e equivalent viscous damping ratio is the damping ratio corresponding to the precast-segment pier when the pier reaches the target displacement under the action of ground motion, but the horizontal displacement amplitude of the pier top is mostly smaller than the target displacement under the action of ground motion.…”
Section: Seismic Design Methods For Hybrid Bridge Structuresmentioning
confidence: 99%
See 2 more Smart Citations
“…(3) Estimating the equivalent viscous damping of the structural system:After installing the viscoelastic damper, the damper further provides additional damping to the structure. e nonlinear hysteretic damping of self-centring structures can be calculated by the hysteretic loop curve obtained from the nonlinear analysis of the structure [16] and the calculation method for the additional damping from viscoelastic dampers based on the method derived in the previous section. (4) Determining the effective viscous damping: e equivalent viscous damping ratio is the damping ratio corresponding to the precast-segment pier when the pier reaches the target displacement under the action of ground motion, but the horizontal displacement amplitude of the pier top is mostly smaller than the target displacement under the action of ground motion.…”
Section: Seismic Design Methods For Hybrid Bridge Structuresmentioning
confidence: 99%
“…(8) Calculating the seismic inertial force corresponding to the target displacement:According to formula (16), the seismic inertial force generated by the target displacement is calculated as follows:…”
Section: A Design Example Of a Hybrid Pier Structurementioning
confidence: 99%
See 1 more Smart Citation
“…Yang et al 16 presented quasi‐static tests on precast post‐tensioned (PT) concrete segmental column specimens with UHPC segment at the bottom and indicated that the specimens were typically nonemulative precast concrete pier and UHPC segment eliminated the damage near the rocking planes. Wang et al 18 conducted the analysis of energy dissipation and self‐centering capacities of PT precast segmental UHPC bridge columns based on the proposed equivalent plastic hinge finite element model, and several design guidelines were suggested. Shafieifar et al 19 proposed an innovative UHPC connection to connect precast column and cap beam in order to shift damage region, increase tolerances, and simplify reinforcement configuration.…”
Section: Introductionmentioning
confidence: 99%
“…The balance between self-centering capacity and energy dissipation capacity is a highlighted issue. Zheng Wang et al [19] pointed out that the increase of the axial compression ratio and the initial pretension stress was an effective way to reduce the residual displacement. Cai Zhong Kui et al [20] proposed a method of using FRP bars as longitudinal bars to reduce the residual displacement after the earthquake.…”
Section: Introductionmentioning
confidence: 99%